Dampak Perubahan Iklim Terhadap Ketahanan Pangan Di Indonesia - Sevina Yushinta Anjani; Bagus Setiawan; Sofi Ayu Nur Martasari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Climate change has a significant impact on global food security, including in Indonesia. The impacts include decreased food production, food crises, increased food prices, and increased health risks. To overcome this challenge, adaptation and mitigation efforts are needed, such as strengthening agricultural infrastructure, developing agricultural technology, increasing the availability of agricultural land, improving the quality of human resources in the agricultural sector, and monitoring food distribution. Indonesia has taken steps to increase food security, including through food estate programs and increasing the use of agricultural technology. However, further efforts are still needed to achieve optimal and sustainable food security.